2021
DOI: 10.1007/s00268-020-05917-0
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Decompression after Cardiac Surgery: Outcome of 42 Patients with Abdominal Compartment Syndrome

Abstract: Background Up to 50% of patients in intensive care units develop intraabdominal hypertension (IAH) in the course of medical treatment. If not detected on time and treated adequately, IAH may develop into an abdominal compartment syndrome (ACS) which is associated with a high mortality rate. Patients undergoing cardiac surgery are especially prone to develop ACS due to several risk factors including intraoperative hypothermia, fluid resuscitation and acidosis. We investigated patients who developed ACS after ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Subsequently, 126 articles were assessed for eligibility via full-text screening, of which 117 articles were further excluded ( Figure 1 ). The final systematic review included nine articles [ 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, 126 articles were assessed for eligibility via full-text screening, of which 117 articles were further excluded ( Figure 1 ). The final systematic review included nine articles [ 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, none of these patients progressed to ACS, possibly due to underpowering of these studies (138 and 69 patients, respectively) (7,9). The incidence and outcomes of perioperative ACS in cardiac surgical patients are less well-described (10)(11)(12)(13). Recently, a prospective observational multicenter study reported one percent of cardiac surgery patients developed ACS post-operatively and require decompressive laparotomy, with significant associated mortality of 57% (13).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and outcomes of perioperative ACS in cardiac surgical patients are less well-described (10)(11)(12)(13). Recently, a prospective observational multicenter study reported one percent of cardiac surgery patients developed ACS post-operatively and require decompressive laparotomy, with significant associated mortality of 57% (13). We could only identify two prior case reports describing the development of intraoperative ACS during cardiac surgery: (1) secondary ACS during failure to maintain CPB while undergoing elective minimally invasive right mini-thoracotomy mitral valve and tricuspid valve repairs (14).…”
Section: Discussionmentioning
confidence: 99%
“…Although increases in IAP occur more commonly in the post-operative period, increases in IAP are known to occur during cardiopulmonary bypass (CPB) and have been implicated in the development of renal failure and mesenteric vascular dysfunction [1,[3][4][5][6][7][8]. The literature on catastrophic IAH and ACS in cardiac surgery, however, is limited to case reports and small studies [9][10][11][12][13]. In one study, the incidence of ACS in cardiac surgery was determined to be about 1% [13].…”
Section: Introductionmentioning
confidence: 99%
“…The literature on catastrophic IAH and ACS in cardiac surgery, however, is limited to case reports and small studies [9][10][11][12][13]. In one study, the incidence of ACS in cardiac surgery was determined to be about 1% [13]. The definitive cause(s) of ACS and catastrophic IAH is not known and remain subject to investigation [2,7,8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%